2014
DOI: 10.1155/2014/376890
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Observations on the Ability to Diagnose and Manage Patients with Asthma through the Use of Impulse Oscillometry: Comparison with Spirometry and Overview of the Literature

Abstract: Objective. Impulse oscillometry (IOS) is an evolving technology for the diagnosis and followup of patients with asthma. Our objective is to review the findings on patients who underwent both spirometry and IOS during clinical evaluations of their asthma. The goal was to retrospectively evaluate IOS during the initial diagnosis and followup of patients with asthma in comparison with spirometry. Methods. We routinely perform IOS and spirometry evaluation in patients with suspected asthma during baseline visits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…We can hypothesize that the global resistance is partly related to a contribution of sputum to luminal airway occlusion. Several studies have also emphasized the potential for FOT to enable better understanding of the complex pathophysiology of obstructive lung diseases such as asthma [ 31 ] and COPD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that the global resistance is partly related to a contribution of sputum to luminal airway occlusion. Several studies have also emphasized the potential for FOT to enable better understanding of the complex pathophysiology of obstructive lung diseases such as asthma [ 31 ] and COPD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…97 More recent studies demonstrated the efficacy of IOS as an alternative to FEV1 in older asthmatic children. 98,99 Interestingly, it has been shown that R5 but not FEV1 showed improvement in patients with persistent asthma after inhaled steroid treatment. 100 Forced oscillation technique holds the perspective of improving Normal values of respiratory impedance (Zrs) for preschool children have been obtained, as well as of respiratory resistance (Rrs).…”
Section: Non-cooperative Patientsmentioning
confidence: 99%
“…Response to treatment can be gauged via handheld nebulizer treatment in the acute setting. In addition, treatment with inhaled corticosteroids or inhaled corticosteroid/LABA or long-acting beta agonists has also been observed independent of spirometry [2]. We will also review the literature regarding the comparison of this modality to traditional spirometry.…”
Section: Overviewmentioning
confidence: 99%